Mutations of the Protocadherin Gene PCDH15 Cause Usher Syndrome Type 1F - Ahmed, Zubair M. (The American Society of Human Genetics, 2001)
Human chromosome 10q21-22 harbors USH1F in a region of conserved synteny to mouse chromosome 10. This region of mouse chromosome 10 contains Pcdh15, encoding a protocadherin gene that is mutated in ames waltzer and causes deafness and vestibular dysfunction. Here we report two mutations of protocadherin 15 (PCDH15) found in two families segregating Usher syndrome type 1F. A Northern blot probed with the PCDH15 cytoplasmic domain showed expression in the retina, consistent with its pathogenetic role in the retinitis pigmentosa associated with USH1F.